Molecular characterization of Anopheline (Diptera: Culicidae) mosquitoes from eight geographical locations of Sri Lanka - Weeraratne, T.C.; Surendran, S.N.; Reimer, L.J.; Wondji, C.S.; Perera, M.D.B.; Walton, C.; Karunaratne, S.H.P.P. (Bio Med Central, 2017)
Background: Genus Anopheles is a major mosquito group of interest in Sri Lanka as it includes vectors of malaria and its members exist as species complexes. Taxonomy of the group is mainly based on morphological features, which are not conclusive and can be easily erased while handling the specimens. A combined effort, using morphology and DNA barcoding (using the markers cytochrome c oxidase subunit I (COI) gene and internal transcribed spacer 2 (ITS2) region, was made during the present study to recognize anophelines collected from eight districts of Sri Lanka for the first time. Methods: Cytochrome c oxidase subunit I and ITS2 regions of morphologically identified anopheline mosquitoes from Sri Lanka were sequenced. These sequences together with GenBank sequences were used in phylogenetic tree construction and molecular characterization of mosquitoes. Results: According to morphological identification, the field-collected adult mosquitoes belonged to 15 species, i.e., Anopheles aconitus, Anopheles annularis, Anopheles barbirostris, Anopheles culicifacies, Anopheles jamesii, Anopheles karwari, Anopheles maculatus, Anopheles nigerrimus, Anopheles pallidus, Anopheles peditaeniatus, Anopheles pseudojamesi, Anopheles subpictus, Anopheles tessellatus, Anopheles vagus, and Anopheles varuna. However, analysis of 123 COI sequences (445 bp) (16 clades supported by strong bootstrap value in the neighbour joining tree and inter-specific distances of >3%) showed that there are 16 distinct species. Identity of the morphologically identified species, except An. subpictus, was comparable with the DNA barcoding results. COI sequence analysis showed that morphologically identified An. subpictus is composed of two genetic entities: An. subpictus species A and species B (inter-specific K2P distance 0.128). All the four haplotypes of An. culicifacies discovered during the present study belonged to a single species. ITS2 sequences (542 bp) were obtained for all the species except for An. barbirostris, An. subpictus species B, An. tessellatus, and An. varuna. Each of these sequences was represented by a single species-specific haplotype. Conclusions: The present study reflects the importance and feasibility of COI and ITS2 genetic markers in identifying anophelines and their sibling species, and the significance of integrated systematic approach in mosquito taxonomy. Wide distribution of malaria vectors in the country perhaps indicates the potential for re-emergence of malaria in the country.
Keywords: Anopheles; DNA barcoding; COI; ITS2; Mosquitoes; Taxonomy; Sri Lanka